Philadelphia, June 1876 Paper - The Hematite Ore Mines and Blast Furnaces East of the Hudson River - James F. Lewis (The American Institute of Mining, Metallurgical, and Petroleum Engineers)
The hematite iron ore mines east of the Hudson River are confined to a strip of country ten to fifteen miles wide, commencing on the south, near Fishkill, running northeast through Dutchess County, and striking the southeast corner of Columbia County, extending into Litchfield County, Conn., known there as the Salisbury mines, cropping out again at and near West Stockbridge, Lanesboro, and Cheshire, Mass., also in Bennington County, Vermont. The ores are found in beds or deposits and in veins, with a limestone ledge on one side and slate on the other, from six to thirty feet from the surface. Portions of it are quite solid, called rock ore, but